CD4:CD8 Ratio and CD8 Count as Prognostic Markers for Mortality in Human Immunodeficiency Virus-Infected Patients on Antiretroviral Therapy: The Antiretroviral Therapy Cohort Collaboration (ART-CC) - Trickey, Adam; May, Margaret T; Schommers, Philipp; Tate, Jan; Ingle, Suzanne M; Guest, Jodie L; Gill, M John; Zangerle, Robert; Saag, Mike; Reiss, Peter; Monforte, Antonella d'Arminio; Johnson, Margaret; et al. (Clinical infectious diseases, 2017)
We investigated whether CD4:CD8 ratio and CD8 count were prognostic for all-cause, AIDS, and non-AIDS mortality in virologically suppressed patients with high CD4 count. We used data from 13 European and North American cohorts of human immunodeficiency virus-infected, antiretroviral therapy (ART)-naive adults who started ART during 1996-2010, who were followed from the date they had CD4 count ≥350 cells/μL and were virologically suppressed (baseline). We used stratified Cox models to estimate unadjusted and adjusted (for sex, people who inject drugs, ART initiation year, and baseline age, CD4 count, AIDS, duration of ART) all-cause and cause-specific mortality hazard ratios for tertiles of CD4:CD8 ratio (0-0.40, 0.41-0.64 [reference], >0.64) and CD8 count (0-760, 761-1138 [reference], >1138 cells/μL) and examined the shape of associations using cubic splines. During 276526 person-years, 1834 of 49865 patients died (249 AIDS-related; 1076 non-AIDS-defining; 509 unknown/unclassifiable deaths). There was little evidence that CD4:CD8 ratio was prognostic for all-cause mortality after adjustment for other factors: the adjusted hazard ratio (aHR) for lower vs middle tertile was 1.11 (95% confidence interval [CI], 1.00-1.25). The association of CD8 count with all-cause mortality was U-shaped: aHR for higher vs middle tertile was 1.13 (95% CI, 1.01-1.26). AIDS-related mortality declined with increasing CD4:CD8 ratio and decreasing CD8 count. There was little evidence that CD4:CD8 ratio or CD8 count was prognostic for non-AIDS mortality. In this large cohort collaboration, the magnitude of adjusted associations of CD4:CD8 ratio or CD8 count with mortality was too small for them to be useful as independent prognostic markers in virally suppressed patients on ART.